2004
DOI: 10.2209/tdcpublication.45.213
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prosthesis Designs and Loading Conditions on the Stress Distribution of Tooth-Implant Supported Prostheses

Abstract: The aim of this study was to observe the influence of prosthesis design and loading condition on the stress distributions of tooth-implant supported prostheses. Six 2D finite element models, two reference models, and four experimental models were computed to simulate different prosthesis designs. Six different loading conditions were applied to investigate the stress distributions of tooth and implant, respectively. The stresses of reference models were considered as 100%; the stresses of experimental models a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…There is a growing belief that implant failure might be caused by disequilibrium of forces acting on the oral implants (Esposito et al, 1998a;Papavasiliou et al, 1996;Petrie and Williams, 2005;Stegaroiu et al, 1998a;Stegaroiu et al, 1998b;Williams et al, 1990;Zhiyong et al, 2004). Although an adaptive remodelling response is observed around dental implants, the biomechanical aspects of these processes remain uncertain (Hoshaw et al, 1994).…”
Section: Implant and Abutment Designmentioning
confidence: 99%
“…There is a growing belief that implant failure might be caused by disequilibrium of forces acting on the oral implants (Esposito et al, 1998a;Papavasiliou et al, 1996;Petrie and Williams, 2005;Stegaroiu et al, 1998a;Stegaroiu et al, 1998b;Williams et al, 1990;Zhiyong et al, 2004). Although an adaptive remodelling response is observed around dental implants, the biomechanical aspects of these processes remain uncertain (Hoshaw et al, 1994).…”
Section: Implant and Abutment Designmentioning
confidence: 99%
“…In contrast, other researchers [21, 7073] found that stresses were mainly concentrated in and around the implant when it was connected to a tooth. Consequently, increasing the number of fixtures rather than abutment teeth, placing minimal loading on teeth, and directing most of the load to implants in order to optimize the stress distribution within the system were recommended.…”
Section: Resultsmentioning
confidence: 82%
“…Especially, the load on the implants show rise with the increase of pontic number. is is the proof of supportation of the prosthesis by the implants [12,24]. Short-term clinical success in tooth-implant-supported and implant-supported prosthesis is similar.…”
Section: Bone Lossmentioning
confidence: 84%
“…ere would be much more movement in the side of implant in tooth-implantsupported bridges with rigid connectors. It was shown that the implants are exposed to much more loading during photoelastic and �nite element analysis [8,24]. Especially, the load on the implants show rise with the increase of pontic number.…”
Section: Bone Lossmentioning
confidence: 99%